Вставлені конструкції в щоденнику Костянтина Москальця «Келія чайної троянди» - Калашник, Юлія; Трифонов, Роман; Kalashnyk, Yulia; Tryfonov, Roman (Східноєвропейський національний університет імені Лесі Українки, 2013)
Визначено структурні та семантичні особливості вставлених конструкцій у мові лірично-філософського щоденника Костянтина Москальця «Келія чайної троянди», класифіковано функції цих синтаксичних засобів у тексті, простежено їхню роль у реалізації прагматичних настанов автора.Structural and semantic characteristics of inserted constructions in the language of lyrical and philosophic diary by Ukrainian writer Kostyantyn Moskalets are defined. The usage of such constructions correlates with the unfolding of thought being verbalized and is, in many respects, one of the style-forming peculiarities of the book. The functions of those stylistic means in the text are classified. The article shows the role of insertions in the creation of intertextual references to precedent phenomena and forming connections between texts. Informational aspect of insertions is also considered as well as their functional load in new information introduction, focusing on details, specification and branching of philosophic reflection. The role of these units is underscored in creation of emotional and evaluative accents. Special attention is paid at metalingual function of inserted constructions serving the clarification of usage, explication of nominative processes and author’s self-positioning in discourse.
Inserted Constructions in Diary «Tea- Rose Cell» by Kostyantyn Moskalets
Keywords: вставлена конструкція; функціональний синтаксис; мова щоденникової прози; експресія; метамова; inserted construction; functional syntax; diary prose language; expressivity; metalanguage